Clarification of the role of 4-methylnonanol, female-produced sex pheromone of the yellow mealworm beetle, Tenebrio molitor (Coleoptera: Tenebrionidae). (January 2017) - Vanderwel, Désirée; Bacala, Cheryl H.; Bacala, Ray; Currie, Robert W.
Abstract: The objective of this study was to clarify the role of (4 R )-(+)-4-methyl-1-nonanol (MNol), a female-produced sex pheromone, in mediating the mating behavior of male Tenebrio molitor L. beetles. The abilities of MNol and authentic female extract (FE) to attract virgin males and to elicit copulatory behavior (CB) from the males were determined by bioassay. Hollow glass rods were used to mimic females. The samples of interest were assayed by coating each either on the outside or on the inside surface of the hollow rods, in order to determine if the responses were due to volatile pheromones (which would be perceived whether coated on the inside or the outside of the rods) or to "contact" pheromones (which would be perceived only when coated on the outside of the rods). The responses of virgin male beetles (6–11 days post-emergence) to FE, MNol, or pentane (control) were compared at both high and low concentrations (n = 10 for each treatment). MNol and the FE showed a similar ability to attract males, at either high or low concentrations. At high concentrations, both MNol and the FE elicited CB from the males. However, unlike the FE, at low concentrations MNol was unable to elicit CB from the males. Thus the FE must contain at least one separate "copulation pheromone" that can elicit the CB at low concentrations. Furthermore, the observed "copulation pheromone" must be volatile, since no difference in response was observed whether the FE was coated on the inside or on the outside surface of the hollow rods. Thus the biological role of MNol is likely to attract males to the females and, once the male is in the immediate vicinity of the female, to act in concert with other pheromones (of which at least one is volatile) to facilitate copulation. Highlights: 4-methylnonanol serves as a female-produced male attractant in Tenebrio molitor. 4-methylnonanol can only elicit copulation behavior at high levels. a volatile pheromone is likely needed in addition to 4-methynonanol to elicit copulation. Thus 4-methylnonanol likely attracts males to females, then facilitates copulation.